Reforming the public administration for food security and agricultural development: Insights from an empirical study in Karnataka - Birner, Regina; Sekher, Madhushree; Raabe, Katharina (International Food Policy Research Institute, 2012)
Strategies to reform rural service provision in India have focused on improving people‘s capacity to demand better services from government agencies. However, efforts to reform the public-sector agencies that provide essential rural services have been limited. Moreover, major knowledge gaps exist on how incentive problems and governance challenges vary across the agencies that provide the services and how they can be addressed. This paper aims to contribute to this knowledge gap. The empirical analysis is based on a survey of 206 field-level staff members of five government departments that provide rural services: Agriculture, Animal Husbandry, Food and Civil Supplies, Women and Child Development, and Rural Development and Panchayati Raj (local government). The paper also draws on a survey of 966 rural households that receive services from these departments. The analysis indicates that there are significant differences across departments regarding the incentives and constraints faced by their frontline service providers. Lack of staff was found to be a major constraint for agricultural and veterinary services, whereas frontline staff in charge of food distribution and civil works experienced political interference as a particularly serious constraint. Contrary to widely held assumptions, availability of funding and administrative procedures was not considered by frontline staff as a major constraint. The findings from the household survey indicate that access and satisfaction with services differ significantly according to caste and gender, even though these effects are not uniform across services. The paper compares the findings of the study with the recommendations of the country‘s Second Administrative Reform Commission and concludes that some constraints, such as political interference, require more attention to make service delivery responsive to the needs of the poor.